Metabolic changes in diet-induced obesity among rats treated with ethanol extract of Alternanthera sessilis red - Othman, Azizah (2016)
Alternanthera sessilis or also known by the name of ‗keremak‘ in Malaysia is a perennial plant that belongs to the plant family of Amaranthaceae. Less research has been conducted on local Alternanthera sessilis species due to its low commercial value. This study was carried out to investigate the nutritional composition, antioxidant capacities and phenolic compounds of Alternanthera sessilis red (ASR) and Alternanthera sessilis green (ASG) in water and ethanolic extracts grown in Malaysia. The ASR has been consumed traditionally as herbal drinks. However, very little scientific data reported about the effect of this plant towards health. Thus, this study was examined the effect of low (175 mg/kg BW) and high (350 mg/kg BW) doses ASR ethanolic extracts supplementation on plasma lipid profile, leptin, adiponectin, liver and kidney function test of diet-induced obesity rats. If an obese rat treated with ASR ethanolic extract, then it will alter the urinary and serum metabolites. Therefore a NMR spectroscopy in conjunction with multivariate analysis was applied to examine metabolite changes and obesity biomarkers in urine and serum of diet-induced obesity rats. The results showed that ASR contained significantly (p < 0.05) higher proximate and mineral contents compared to ASG. Ethanolic extracts of both ASR and ASG presented significantly greater antioxidant capacity, than the water extracts at p < 0.05. Total phenolic content exhibited a positive correlations with antioxidant capacities which could be one of the critical contributors to the antioxidant activity. A total of eleven phenolic compound were identified in ASR extract. The phenolic compound in ASR extract were gallic acid, epigallocatechin, catechin, chlorogenic acid, 4-hydroxybenzoic acid, vanilic acid, ferulic acid, ethyl gallate, myricetin, daidzein and apigenin. The low dose ASR extract significantly improved plasma lipid profile and decreases leptin level after eight weeks of daily therapy. While obese rats treated with high dose ASR extract have significantly fewer visceral fat mass compared to other studied groups. Obesity due to high fat diet led to an increase in urinary glucose, creatinine, serotonin and 3-hydroxybutyrate; however, ASR extract reduces the 2-hydoxybutyrate, alanine, allantoin, beta-glucose and N6-acetyllysine after eight weeks of daily therapy. In serum, glycerol, 3-hydroxybutyrate, methionine and glucose were found higher in diet-induced obesity rats compared to lean rats; however, serum glucose and glycerol were reduced after treated with ASR extract. Furthermore, score plots of partial least-squares discriminant analysis showed 50% of obese rats treated with low dose ASR extract was normalised. This finding is consistent with the result obtained from urine and biochemical analyses of plasma, thus indicating that low dose ASR is more effective than high dose in reversing lipid profile and glucose towards normal levels. The lipid lowering effect of ASR extract might be contributed by ferulic acid, which has the ability as HMG-CoA reductase inhibitor and leads to the decrement of LDL cholesterol. The results of the present study demonstrates that low dose ASR extract exhibited anti-hyperlipidaemia, leptin and glucose reversing effects of diet-induced obesity rats, thus may be a useful therapeutic candidate for hyperlipidaemia.